Molecular detection and antibiotic resistance of diarrheagenic Escherichia coli from street food and water in mukuru slums, Nairobi County - Sheillah Mundalo; Regina Ntabo; Kelvin Kering; Rael Too; Kevin Kariuki; Diana Imoli; Brian Silantoi; Evans Kiptanui; Susan Kavai; Samuel Kariuki; Cecilia Mbae (PLoS ONE, 2026)
Globally, diarrheal diseases account for 550 million cases of foodborne illnesses annually. In Kenya, Escherichia coli ( E. coli ) infections from contaminated food and water pose a serious health concern, especially in settings with poor sanitation and hygiene practices This study examined the genetic characteristics and antimicrobial resistance profiles of diarrheagenic E. coli (DEC) recovered from street foods and water from Mukuru informal settlements, Nairobi. Between September and December 2023, 384 (each 77) samples of street foods ( Mandazi, githeri, French fries ), wastewater, and drinking water were collected and E . coli isolation performed through microbiological culture and antibiotic susceptibility testing done using Kirby-Bauer disc diffusion method. Conventional Polymerase chain reaction (PCR) was used to screen for six DEC and extended-spectrum beta-lactamase (ESBL) resistance genes. Descriptive and inferential statistics (Pearson’s chi-square test) were used to assess associations between sample types, E. coli positivity, pathotypes, and antibiotic resistance. E. coli was isolated in 16% (62/384) of the samples , with 77.4% (48/62) of the isolated E. coli being DEC. Majority (64.6%, 31/48) of DEC isolates were recovered from wastewater followed by drinking water (22.9%, 11/48), githeri ( 8.3%, 4/48), mandazi (4.2, 2/48), and none from french fries . The most common pathotypes were; ETEC 69% (33/48), STEC 52.1% (25/48), EIEC 50% (24/48)), EPEC 10% (5/48), and EAEC 6% (3/48) Of the 48 DEC isolates, 30 were hybrid isolates Overall, the E. coli isolates were highly resistant to tetracycline (77.4%), trimethoprim-sulfamethoxazole (71.0%), ampicillin (59.7%) and least resistant to kanamycin (16.1%); chloramphenicol (8.1%) and amoxicillin + clavulanic acid (4.8%). A huge proportion (72.6%, 45/62) of the isolated E. coli were multidrug-resistant (MDR). Of the 45 MDR isolates, 60% (27) were from wastewater, 28.9% (13) from drinking water, 4.4% (2) from githeri, 4.4% (2) from mandazi and 2.2% (1) french fries 2.2%. ESBL genes bla - TEM and bla CTX-M were detected in 12.9% and 3.2% of the E. coli isolates. isolates. The high prevalence of MDR in the E.coli isolates recovered from environmental compartments and food is a huge public health risk to the population in these settings. The detection of E. coli indicates fecal contamination underscoring the need to improve water, and sanitation infrastructure in urban slums.